Lung Tumorigenesis Alters the Expression of Slit2-exon15 Splicing Variants in Tumor Microenvironment - Wu, Ming-Fang; Chuang, Cheng-Yen; Lin, Pinpin; Chen, Wei-Ting; Su, Shang-Er; Liao, Chen-Yi; Jan, Ming-Shiou; Chang, Jinghua Tsai (Cancers, 2019)
Slit2 expression is downregulated in various cancers, including lung cancer. We identified two Slit2 splicing variants at exon15—Slit2-WT and Slit2-ΔE15. In the RT-PCR analyses, the Slit2-WT isoform was predominantly expressed in all the lung cancer specimens and in their normal lung counterparts, whereas Slit2-ΔE15 was equivalently or predominantly expressed in 41% of the pneumothorax specimens. A kRasG12D transgenic mice system was used to study the effects of tumorigenesis on the expressions of the Slit2-exon15 isoforms. The results revealed that a kRasG12D-induced lung tumor increased the Slit2-WT/Slit2-ΔE15 ratio and total Slit2 expression level. However, the lung tumors generated via a tail vein injection of lung cancer cells decreased the Slit2-WT/Slit2-ΔE15 ratio and total Slit2 expression level. Interestingly, the lipopolysaccharide (LPS)-induced lung inflammation also decreased the Slit2-WT/Slit2-ΔE15 ratio. Since Slit2 functions as an anti-inflammatory factor, the expression of Slit2 increases in kRasG12D lungs, which indicates that Slit2 suppresses immunity during tumorigenesis. However, an injection of lung cancer cells via the tail vein and the LPS-induced lung inflammation both decreased the Slit2 expression. The increased Slit2 in the tumor microenvironment was mostly Slit2-WT, which lacks growth inhibitory activity. Thus, the results of our study suggested that the upregulation of Slit2-WT, but not Slit2-ΔE15, in a cancer microenvironment is an important factor in suppressing immunity while not interfering with cancer growth.